Mentawai Natural Environment Ornament Transformation on Batik Art Tatoo Motivation Based on Local Wisdom: Ecotourism - Agusti Efi; Budiwirman; Yusmerita; Sri Zulfia Novrita; Yulia Aryati; Gabila Heira Mutia (Jurnal Penelitian Pendidikan IPA, 2023)
The people of the Siberut Mentawai islands still maintain various arts and practice the culture and customs of their ancestors. They have natural environment ornaments including tattoos and Jaraik, which is a symbol of the greatness of the Sikerei (Shaman) house in the Mentawai tribe.Â  Along with the progress and development of the Mentawai area, traditional culture began to shift, therefore it is necessary to carry out conservation and development efforts. So, the purpose of this research is the efforts to preserve and produce creative art products based on local wisdom by transforming tattoos, jaraik, and other Mentawai natural environments in batik art and uniting various elements of visual cultural arts as supporting elements. The method used is research and development adopting the 4 D steps with four stages of development design, development, and deployment. In addition, the study also conducted studies of art and aesthetics, design and fashion as well as analysis of market tastes. So, the outputs of this research are; prototypes of batik art innovation products based on local Mentawai culture that are market-worthy; and scientific articles in reputable international journals. Focus Group Discussion (FGD) and product feasibility tests were carried out by experts and product exhibitions which were used as Mentawai branding. Â